2006
DOI: 10.4161/hv.2.4.2943
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination and Risk of Incident Myocardial Infarction

Abstract: Background: Several studies suggest that influenza vaccination may be associated with a decreased risk of acute cardiovascular events. We examined the association between influenza vaccination and risk of incident myocardial infarction (MI) in persons at least 65 years of age in a population-based case-control study.Methods: Case subjects were members of Group Health Cooperative (GHC), a health maintenance organization, with incident MI during 1992-1998. Control subjects were GHC members without a history of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 25 publications
1
28
0
1
Order By: Relevance
“…A recent case-control study found no association between stroke and influenza vaccination, 8 and negative results have also been found in the prevention of myocardial infarction. [24][25][26] There is also the possibility that, because of publication bias, other negative studies have not been published. However, above all, observational studies may be biased and this is particularly true for influenza vaccination studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent case-control study found no association between stroke and influenza vaccination, 8 and negative results have also been found in the prevention of myocardial infarction. [24][25][26] There is also the possibility that, because of publication bias, other negative studies have not been published. However, above all, observational studies may be biased and this is particularly true for influenza vaccination studies.…”
Section: Discussionmentioning
confidence: 99%
“…10,18 Studies with no evidence of benefit had low power, poor case ascertainment, misclassification of vaccination status and lack of investigator blinding. [19][20][21] The additional benefit of early within-season influenza vaccination (i.e., during the period from September to mid-November) compared with late vaccination (i.e., after mid-November) has been suggested by findings of previous research, 22 but is not part of current recommendations for influenza vaccination. 23 Given that influenza vaccination is likely to be effective only against circulating strains of influenza virus, our findings are strengthened by the biological plausibility of a within-season or within-year effect of influenza vaccination in preventing influenza-related acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study was likely underpowered because of the small proportion of patients with a history of CVD. The 2 matched case-control studies 26,27 were heterogeneous with regard to results: one showed a benefit with influenza vaccine, whereas the other was neutral. However, both of these studies were limited by differences in baseline characteristics that were not adjusted for in the analyses.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] All 3 studies were deemed to be of low or very low quality according to the GRADE criteria.…”
Section: Nonrandomized Studiesmentioning
confidence: 99%
See 1 more Smart Citation